Anticoagulant and Fibrinolytic Properties of Two Heparinoid Compounds Prepared from Shrimp Waste - Jing Chen; Zhuo Wang; Xuejing Jia; Rui Li; Jianping Chen; Xiaofei Liu; Bingbing Song; Saiyi Zhong; Yi Qi (Foods, 2022)
Heparinoid, a type of compound that has structures similar to heparin, has been found in marine organisms such as shrimp head. This shrimp waste products were used to prepare, characterize, and evaluate the antithrombotic effect of heparinoid. Two heparinoid compounds were obtained from shrimp head, and the main fraction F1 was →4)-GlcA-(1→3)-GalNAc-(1→ with Ara, while the minor fraction F2 composed mainly of the backbone as →4)-β-D-GlcA (or IdoA)-(1→4)-β-D-GlcN (or GlcNAc)-(1→. Both F1 and F2 could extend activated partial thromboplastin time and thrombin time concentration-dependently, and F2 has stronger activity than F1 at the same concentration. The potential anticoagulant mechanism of F1 and F2 may relate to their combination with more antithrombin III, which binds to and potentiates the action of antithrombin as well as inhibiting coagulation factors Xa and IIa, preventing blood clot formation. Furthermore, heparinoid F1 and F2 were found to have high fibrinolytic capability in vitro and in vivo via activating the self-fibrinolytic system. In conclusion, heparinoids (F1 and F2) derived from shrimp head wastes could be used as candidate compounds to prevent thrombosis while posing a lower hemorrhagic risk.